Effect on Profitability Liquidity Management of Banking Companies in Indonesia Stock Exchange - Sinarti Sinarti; Fitriah Rahmadany (Pusat P2M Politeknik Negeri Batam, 2018)
This study examines the impact of liability (quick ratio) to profitability in banking companies listed in Indonesia Stock Exchange (BEI) to prove its influence on the level of debt repayment banking finance company. The data used in this research is secondary data uses financial statements that have been audited. Data analysis technique used is simple regression analysis. The results indicate that the quick ratio positive effect on the company's financial profitability. The results of this study illustrate that the liability would affect the profitability of companies that are in financial companies to be used effectively and efficiently. This research is important for companies and organizations, in order to better the use or utilization liability. The company is only limited to the banking companies listed in BEI, then further research is recommended to add criteria and indiktor others that have not been addressed in this study, in addition to subsequent authors can also extend the sample population to another company with a different field such as manufacturing or services.